Application of machine learning to predict quality of Portuguese wine based on sensory preferences - Nascimento, Alsénvitor Campos Aires do (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence